2014
DOI: 10.1136/amiajnl-2014-002686
|View full text |Cite
|
Sign up to set email alerts
|

The long-term financial impact of electronic health record implementation

Abstract: Practice reimbursements increased after EHR implementation, but there was a long-term decrease in the number of patient visits seen in this ambulatory practice context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 17 publications
3
28
0
Order By: Relevance
“…In one study, costs were recaptured within 16 months, with ongoing annual savings and no adverse effect on efficiency 97. In another, overall productivity increased by around 5% per year post-full EPR implementation98; whilst productivity may initially fall, billing income may increase due to improved coding 99. Furthermore, cost-savings include reduced medication errors, improved implementation of clinical practice guidelines, enhanced infection prevention and cost-effective diagnostic testing100; order-set creation and care pathway redesign have significant benefits 101.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, costs were recaptured within 16 months, with ongoing annual savings and no adverse effect on efficiency 97. In another, overall productivity increased by around 5% per year post-full EPR implementation98; whilst productivity may initially fall, billing income may increase due to improved coding 99. Furthermore, cost-savings include reduced medication errors, improved implementation of clinical practice guidelines, enhanced infection prevention and cost-effective diagnostic testing100; order-set creation and care pathway redesign have significant benefits 101.…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that the longer-time productivity and financial performance of the study practices were not affected by the EHR implementation; however, the short-term negative impact was evident. In another study, Howley et al (2015) analyzed the productivity and reimbursement data collected longitudinally from 30 ambulatory care practices for 2 years after implementing an EHR system [142]. The authors found that, by comparing each site to their pre-EHR baseline, the study practices saw fewer patients with the EHR, but their reimbursements significantly increased.…”
Section: G Financial Impactmentioning
confidence: 99%
“…eHealth includes a broad array of health-related information and communication technologies (ICT) such as electronic health records, electronic prescribing systems, health information exchange systems and clinical decision support systems. Several studies have indicated that the use of eHealth technologies can lead to potential benefits in improving the quality and delivery of healthcare services, enhancing cost savings, increasing revenue, facilitating patient safety, reducing waiting times and create greater patient engagement during the course of their care [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%